Regulatory Aspects and Problems of Personnel Certification Taking into Account the Requirements of Professional Standards - A. Zaitseva , Natalia; A. Larionova , Anna; I. Shapovalov, Nikolay; V. Povorina, Elena; V. Takhumova, Oksana; A. Zhukova , Marina; A. Dvornikova, Tatiana (International Journal of Psychosocial Rehabilitation, 2020)
In the national system of professional qualifications now being created in Russia, the role of professional standards is quite large, both for training personnel and for assessing the competencies of graduates of educational organizations and for independent assessment of the qualifications of employees. The relevance of the study of the problems of personnel certification taking into account the requirements of professional standards is determined by the need to improve the regulatory framework for improvement in order to expand the practice of applying professional standards. The aim of the article is to find ways to solve the problems of applying professional standards for the certification of personnel in the Russian Federation. As a result of the study, the authors of the article substantiated the main differences in the legislative regulation of personnel certification based on the use of professional standards in the Russian Federation, formulated the goals and objectives of personnel certification on the example of certain types of professional activity, and identified and formulated the main problems of applying professional standards for the purposes of personnel certification. The results of this study can be useful in developing a set of measures to improve personnel potential, both at the level of individual enterprises and at the regional level.